2002
DOI: 10.1073/pnas.0135345100
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional synaptic plasticity in the cerebellum-like mammalian dorsal cochlear nucleus

Abstract: The dorsal cochlear nucleus integrates acoustic with multimodal sensory inputs from widespread areas of the brain. Multimodal inputs are brought to spiny dendrites of fusiform and cartwheel cells in the molecular layer by parallel fibers through synapses that are subject to long-term potentiation and long-term depression. Acoustic cues are brought to smooth dendrites of fusiform cells in the deep layer by auditory nerve fibers through synapses that do not show plasticity. Plasticity requires Ca 2؉ -induced Ca … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
137
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(151 citation statements)
references
References 46 publications
11
137
3
Order By: Relevance
“…The latter effect might be (at least partly) the consequence of the elimination of the short-term depression present at the parallel fibre-giant cell synapses. Since cholinergic activity simultaneously increases the firing activity of the granule cells, the cholinergic stimulation may contribute to shifting the plasticity of these synapses towards long-term potentiation, similarly to that shown in the cases of the parallel fiber-pyramidal neurone synapses [9].…”
Section: Muscarinic Modulation Of Dcn Granule Cellsmentioning
confidence: 77%
“…The latter effect might be (at least partly) the consequence of the elimination of the short-term depression present at the parallel fibre-giant cell synapses. Since cholinergic activity simultaneously increases the firing activity of the granule cells, the cholinergic stimulation may contribute to shifting the plasticity of these synapses towards long-term potentiation, similarly to that shown in the cases of the parallel fiber-pyramidal neurone synapses [9].…”
Section: Muscarinic Modulation Of Dcn Granule Cellsmentioning
confidence: 77%
“…Because ERK and PKA activity can be regulated by paradigms that generate synaptic plasticity, it is possible that plasticity mechanisms, including those showing sensitivity to spike timing (Bell et al 1997;Feldman 2000;Magee and Johnston 1997;Markram et al 1997;Zhang et al 1998), alter not only synaptic strength, but via actions on specific ion channels also change the relationship between synaptic inputs and spike generation. Such a mechanism could operate in addition to the recently shown synaptic plasticity at the parallel fiber synapses (Fujino and Oertel 2003;Tzounopoulos et al 2004). …”
Section: Potential Plasticity Of the Timing Encoding Mechanismmentioning
confidence: 99%
“…Many studies identified a significant increase in spontaneous burst frequencies in DCN in cases of tinnitus; others highlighted the multi-layer and organized structure of DCN that facilitated synaptic plasticity induction, such as LTP and long-term depression. LTP can be evoked by an appropriate HFS in fusiform cells because of their cellular and synaptic characteristics [7,15,16] . Synaptic plasticity is classified into long and short term, according to the duration of re-modeling [17] .…”
Section: Discussionmentioning
confidence: 99%
“…The arithmetic averages of the baseline EPSCs and post-HFS EPSCs between the 5.5 and 10th, 10.5 and 15th, and 15.5 and 20th min were calculated. An increase of ≥10% of post-HFS 5.5th-and 20th-min period according to the baseline EPSCs was referred to LTP generation [7] . LTP recordings were stable during the experiment.…”
Section: Electrophysiological Protocolmentioning
confidence: 99%
See 1 more Smart Citation